Reappraisal of ANK2 Variants in Cardiovascular Diseases: Uncovering Mechanisms and Future Directions - Linjuan Guo; Dexi Wu; Wengen Zhu (Reviews in Cardiovascular Medicine)
Inherited cardiac arrhythmias, which may lead to sudden cardiac death, represent a significant health risk, with genetic factors playing a key role in their development. The ankyrin 2 (ANK2) gene, encoding ankyrin-B, is implicated in several heritable arrhythmia syndromes. ANK2 variants have been linked to an inherited condition known as “ankyrin-B syndrome”, which manifests as a spectrum of cardiac arrhythmias and cardiomyopathy. Our current review examines the relationship between ANK2 variants and specific heart conditions, summarizing recent findings on the genetic and molecular mechanisms underlying ANK2-related arrhythmias and structural abnormalities. By emphasizing the need for further research, this review aims to enhance understanding of ANK2’s role in heart disease and guide the development of effective therapies.